CURRENT EPIDEMIOLOGY OF LICHEN SIMPLEX CHRONICUS - Filka Georgieva (Journal of IMAB, 2016)
Background Lichen Simplex Chronicus (LSC) is a common extremely pruritic dermatoses affecting seriously the wellbeing of patients. Although the diagnosis is easily confirmed the therapy is still a challenge for specialists. The aim of the study was to update the epidemiology of LSC. Objective and Methods To assess the tendencies in distribution of LSC were analyzed data collected from registers of Medical Centre “St. Anna” Varna from January 2007 till July 2015. Data include reports of 39968 outpatients with different skin problems. The model of the study was retrospective and investigates the total morbidity, gender distribution, age distribution, peak condition and place of the disease in the structure of selected chronic recurrent dermatoses with negative impact on quality of life. Data were collected and processed after obtaining written permission from the leadership of MC “St. Anna" Varna. Results. The overall frequency of LSC was 4.04%. It increased from 2.59% (2007) to 4.62% (2015). Results show a tendency of rejuvenation of LSH with two peaks of morbidity: over 65 years of age 11.87% and second in the range 25-30 years -10.77%.The the ratio female / male is established to 1.2: 1.The distribution analysis shows the prevalence of LSC in winter season – January 5.14%, February – 4.57% and low morbidity in summer mouths - July 1.92% and August 0.66%. (p = 0.001) The distribution of LSC was compared with that of several skin diseases with a chronic course and a negative influence on the quality of life of patients. Results show increasing of LSC from 3.36% (2008) to 4.55% (2014) (p = 0.001). Conclusion This is the first study in our country, which aims to update the epidemiology of LSC.